An attempt for analysing the agricultural performance and potential in Romania on NUTS3 county level - Bíró, Bíborka-Eszter; Bíró, Boróka-Júlia (Észak-magyarországi Stratégiai Füzetek, 2024)
Present study proposes to give a snapshot view on the Romanian agriculture regarding its potential and performance. The analysis is made with recent datasets referring to the year 2020. County level (NUTS3) calculations have been made to give a more detailed view of the territorial diversity of the Romanian agriculture. A scoring model had been constructed in order to reflect the agricultural potential and performance level of each Romanian county.